PENTINGNYA MELAKUKAN PERSONAL BRANDING DAN MEMAHAMI DIGITAL MARKETING PADA PEDAGANG PASAR TRADISIONAL KARANGAMPEL INDRAMAYU - Marfua Suebudin (LPPM STKIP Pangeran Dharma Kusuma Segeran Juntinyuat Indramayu, 2022)
Karangampel Market is the central market for Karangampel District, Juntinyuat District, Kedokan Bunder District and Krangkeng District. So that the Karangampel Market is always crowded with buyers every day, but because of the Covid-19 pandemic it has an impact on economic activity in the Karangampel Market. This resulted in a decrease in the number of traders' income. This research started from the problem of declining sales which had an impact on the income felt by Karangampel traditional market traders due to the covid-19 pandemic. However, on the other hand, there are other business actors outside the traditional Karangampel market who have actually experienced an increase in sales turnover during this pandemic. From these problems, the purpose of this study is to find out whether personal branding and digital marketing knowledge can affect the increase in sales turnover. This study uses qualitative research methods, the type of research is field research with a descriptive approach. Data collection techniques through observation, interviews and documentation. Data analysis techniques are analysis before the field and data analysis in the field with the stages of data reduction, data presentation, and drawing conclusions. Test the validity of the data using source triangulation. The results showed that doing personal branding, and understanding knowledge and applying digital marketing had an effect on sales turnover